A Comprehensive Analysis of Alterations in DNA Damage Repair Pathways Reveals a Potential Way to Enhance the Radio-Sensitivity of Esophageal Squamous Cell Cancer - Wang, Guangchao; Guo, Shichao; Zhang, Weimin; Li, Zhangfu; Xu, Jiancheng; Li, Dan; Wang, Yan; Zhan, Qimin (Frontiers in Oncology, 2020)
Esophageal squamous cell cancer (ESCC) is a common malignancy with a poor 5-year overall survival in China. Altered DNA damage repair (DDR) pathways are associated with a predisposition to cancer and contribute to therapeutic response and resistance in cancers. However, alterations of DDR pathway genes in ESCC are still largely unknown. In this study, we employed genome sequencing data of 192 samples, comparative genomic hybridization data of 123 cases and gene expression microarray data of 119 patients to firstly perform a comprehensive analysis of the gene alterations of 7 DDR pathways in ESCC. Gene mutations and copy number variations (CNVs) were observed in all 7 DDR pathways, and especially, CNVs were the dominant alteration types. Compared with other pathways, two DNA double-strand break (DSB) repair pathways homologous recombination (HR) and non-homologous end joining (NHEJ), carried significant gene mutations and CNVs especially gene amplifications. Most genes including RAD54B, NBS1, RAD51B and PRKDC were significantly amplified and overexpressed in ESCC. Amplification and high expression of DSB repair pathway genes were associated with poorer overall survival. Gene set variation analysis further showed that DSB repair pathways were up-regulated in ESCC. Besides, we firstly demonstrated that combination of mirin and NU7441, two inhibitors for HR and NHEJ respectively, with ionizing radiation treatment significantly enhanced DSBs, reduced clonogenic cell survival, inhibited cell proliferation and promoted cell apoptosis in ESCC cells with DSB pathway gene amplification. These findings suggest that DSB repair pathways were significantly altered in ESCC and inhibiting DSB repair pathways might enhance the radio-sensitivity of ESCC with DSB repair up-regulation.